2014
DOI: 10.1002/hed.23739
|View full text |Cite
|
Sign up to set email alerts
|

Determination of biometric measures to evaluate patient suitability for transoral robotic surgery

Abstract: Mandibular body height, hyoid-mental length, and neck circumference in conjunction with the degree of mouth opening may determine patient suitability for TORS. Clinical evaluation is essential to validate their collective usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Lim et al 70 evaluated the anatomy of the oropharynx and identified the key landmarks, including the glossopharyngeal nerve, styloglossus muscle, and external carotid artery, and explained that highlighting these key anatomic landmarks during training may help to shorten the learning curve of the TORS procedure. Arora et al 71 evaluated patient selection for the procedure, which is currently qualitatively assessed by exam under anesthesia. However, a number of quantitative biometrics are already being used to predict the difficulty of intubation, and similar objective measurements exist in which to better guide the surgical approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al 70 evaluated the anatomy of the oropharynx and identified the key landmarks, including the glossopharyngeal nerve, styloglossus muscle, and external carotid artery, and explained that highlighting these key anatomic landmarks during training may help to shorten the learning curve of the TORS procedure. Arora et al 71 evaluated patient selection for the procedure, which is currently qualitatively assessed by exam under anesthesia. However, a number of quantitative biometrics are already being used to predict the difficulty of intubation, and similar objective measurements exist in which to better guide the surgical approach.…”
mentioning
confidence: 99%
“…The incorporation of this practice may decrease surgical morbidity through better selection of TORS candidate patients by removing qualitative predictions and variability between surgeons. 71 …”
mentioning
confidence: 99%
“…We only used the FKWO retractor for hypopharyngeal exposure; no other gags such as Davis gag was used. However, visualization of the epiglottis was significantly better using the FK retractor compared to the Davis gag [18]. Thus, evaluation with the FKWO retractor in this study was appropriate.…”
Section: Discussionmentioning
confidence: 88%
“…Inadequate target exposure that could not permit TORS was reported to occur in 7-26% of cases [2,17]. Identifying patients who are unsuitable is crucial to preventing unnecessary general anesthesia and minimizing the time and financial costs of abandoned TORS and conversion to open surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…Initial indications for TORS involved base of tongue neoplasms, but, with increasing experience combined with preclinical studies on animals and cadavers, these rapidly expanded [17]. Currently, TORS constitutes a valuable treatment modality for tumours of the oropharynx (including advanced oropharyngeal carcinoma) [18], hypopharynx [19], parapharyngeal space [20], and supraglottic larynx [21].…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%